World Economic Outlook, April 2013 : Hopes, Realities, Risks. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2013)
Global economic prospects have improved again, but the bumpy recovery and skewed macroeconomic policy mix in advanced economies are complicating policymaking in emerging market economies. Chapter 3 examines the prospects for inflation, particularly because inflation was remarkably stable in the wake of the Great Recession and, in fact, has become less responsive to cyclical conditions. Chapter 4 examines whether today's fast-growing, dynamic low-income countries are likely to maintain their momentum and avoid the reversals that afflicted many such countries in the past.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet